Captopril Renal Scintigraphy in Screening and Diagnosis of Renal Artery Stenosis - A Prospective Study - Rauniyar, RK; Bal, CS; Kumar, R; Srivastava, DN; Dash, SC; Gupta, A; Berry, M (Nepalese Journal of Radiology, 2013)
The present study was carried out to assess the role of Tc99m-DTPA captopril renal scintigraphy in screening and diagnosing of patients with renal artery stenosis. Materials and Methods: A total of 26 hypertensive patients with a clinical suspicion of RAS underwent baseline and captopril scintigraphy using 259-370 MBq (7-10mCi) of Tc99m-DTPA. The captopril scintigraphy was done after oral dose of 50mg of captopril with in three baseline study. DSA was done in all patients irrespective of scintigraphy results due to high clinical suspicion of RAS. Results: Of 26 patients, 18 had renal artery stenosis (10 unilateral, 8 bilateral), making a total of 26 involved RA on DSA. Of these 26 involved RA, 16 were stenosis> 60%, 2 were stenosed< 60% while 8 were completely occluded. Of the sixteen RA with stenosis > 60%, only 12 were detected by captopril scintigraphy (Sensitivity-75%). Eight kidneys with complete occlusion, 6 were non-functioning and 2 were poorly functioning (<20%) on scintigraphy. Among 27 normal RA, (25 normal and two <60% stenosis) only 19 were negative on scintigraphy (specificity-70%). Two kidneys with less than 60% stenosis were positive on scintigraphy. The overall accuracy of captopril DTPA scintiography was found to be 72.1% with PPV and NVP of 66.7% and 82.6% respectively. Two patients with accessory RA were not picked up on captopril scintigraphy. Conclusion: Tc99m-DTPA captopril scintigraphy has average sensitivity and specificity. The effectiveness of captopril scintigraphy in diagnosis of completely occuluded RA, accessory RAS and RAS in poorly functioning kidney is poor, therefore this test cannot be considered as screening test for RVH. Nepalese Journal of Radiology; Vol. 2; Issue 2; July-Dec. 2012; 28-35 DOI: http://dx.doi.org/10.3126/njr.v2i2.7682